2022
DOI: 10.3390/genes13101699
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Function and Crosstalk with Other Phytohormones under Normal and Stressful Conditions

Abstract: Melatonin was discovered in plants in the late nineties, but its role, signaling, and crosstalk with other phytohormones remain unknown. Research on melatonin in plants has risen dramatically in recent years and the role of this putative plant hormone under biotic and abiotic stress conditions has been reported. In the present review, we discuss the main functions of melatonin in the growth and development of plants, its role under abiotic stresses, such as water stress (waterlogging and drought), extreme temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 122 publications
1
39
0
Order By: Relevance
“…More recent research has begun to uncover the novel roles of chloroplasts in plant growth and development. Melatonin produced in chloroplasts and mitochondria is important for plants under stress conditions [ 10 ]. The COP1LIKE protein acts as a repressor of photomorphogenesis and plays roles in the reproductive development and light-dependent pigment accumulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent research has begun to uncover the novel roles of chloroplasts in plant growth and development. Melatonin produced in chloroplasts and mitochondria is important for plants under stress conditions [ 10 ]. The COP1LIKE protein acts as a repressor of photomorphogenesis and plays roles in the reproductive development and light-dependent pigment accumulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Except for tomatoes, our findings imply that ZF-HD/ZHD family genes have been largely conserved in evolution, along with their functions. In previous studies of ZF-HD/ZHD genes in other plants, researchers have concluded that these genes have undergone severe purifying selection, and their functions cannot be differentiated [ 42 , 48 , 49 , 50 , 51 , 52 ]. Motif analysis showed various conserved motifs of ZmZHD proteins in Classes I and II, revealing similar motifs present in the same subclass in the phylogenetic tree that are functionally similar ( Figure 3 A,C).…”
Section: Discussionmentioning
confidence: 99%
“…Among other types of plant secondary metabolites, an example is melatonin, which is derived from tryptophan and was initially isolated from animals before being discovered in plants. Melatonin plays an important role in plant growth and development as well as the response to biotic and abiotic stress; in addition, it has strong antioxidant activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%